2019
DOI: 10.7554/elife.44912
|View full text |Cite
|
Sign up to set email alerts
|

A switch in surface polymer biogenesis triggers growth-phase-dependent and antibiotic-induced bacteriolysis

Abstract: Penicillin and related antibiotics disrupt cell wall synthesis to induce bacteriolysis. Lysis in response to these drugs requires the activity of cell wall hydrolases called autolysins, but how penicillins misactivate these deadly enzymes has long remained unclear. Here, we show that alterations in surface polymers called teichoic acids (TAs) play a key role in penicillin-induced lysis of the Gram-positive pathogen Streptococcus pneumoniae (Sp). We find that during exponential growth, Sp cells primarily produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(78 citation statements)
references
References 84 publications
7
71
0
Order By: Relevance
“…We have shown that S. aureus WTA levels increase substantially when LTA levels are low. This finding is reminiscent of findings in Streptococcus pneumoniae showing that levels of WTA and LTA are inversely regulated (57). S. pneumoniae synthesizes both forms of teichoic acid through the same pathway, with the outcome distinguished only by a final ligation step where the polymer precursor is transferred to PG or to a glycolipid (58).…”
Section: Discussionsupporting
confidence: 74%
“…We have shown that S. aureus WTA levels increase substantially when LTA levels are low. This finding is reminiscent of findings in Streptococcus pneumoniae showing that levels of WTA and LTA are inversely regulated (57). S. pneumoniae synthesizes both forms of teichoic acid through the same pathway, with the outcome distinguished only by a final ligation step where the polymer precursor is transferred to PG or to a glycolipid (58).…”
Section: Discussionsupporting
confidence: 74%
“…Lama et al (2012) found that when amicoumacin A was exposed to MRSA, it reduced the activity of murein hydrolase, called autolysin, which was highly needed in the regulation of continued wall extension and cellular division (Higgins et al, 1970;Gilpin et al, 1972). The recent research demonstrated that the mode of action of penicillin-induced explosive lysis of Streptococcus pneumonia, a decades-long puzzle, was also because of autolysin disorder (Flores-Kim et al, 2019). Interestingly, with the assistance of confocal microscopy and scanning electron microscopy, Gao et al (2017) found that amicoumacin A, secreted by a marine probiotic strain, can damage the surface structure of V. vulnificus cells, as reflected by the formation of cell cavities, the presence of membrane holes, and consequent cell lysis.…”
Section: Discussionmentioning
confidence: 99%
“…It was believed previously that the PBP loss of function was directly bactericidal. PBP inactivation by β‐lactams is seen now as the triggering event that initiates more complex, and perhaps even species‐specific, pathways that culminate in bactericidal cell lysis . Perhaps as a consequence (but at the molecular level, for reasons not understood) some resistance mechanisms against the β‐lactams exert a cellular cost.…”
Section: Miraculous Chemistrymentioning
confidence: 99%
“…PBP inactivation by β-lactams is seen now as the triggering event that initiates more complex, and perhaps even species-specific, pathways that culminate in bactericidal cell lysis. [115][116][117][118][119][120] Perhaps as a consequence (but at the molecular level, for reasons not understood) some resistance mechanisms against the β-lactams exert a cellular cost. The notorious Grampositive pathogen S. aureus does not activate its resistance mechanisms until it detects the presence of a β-lactam.…”
Section: Miraculous Chemistrymentioning
confidence: 99%